Pengaruh Kemandirian Mahasiswa dan Perilaku Ekonomi Terhadap Perencanaan Uang Saku Penerima Beasiswa KIP-K Prodi Pendidikan Ekonomi - Uswatul Musarrofah; Sugeng Pradikto (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research is to analyze the influence of student autonomy and financial behavior on planning pocket money for students receiving the KIP-K scholarship for the Business Education undergraduate program at PGRI Wiranegara University. The research method used is a quantitative approach with a correlational design. Data was collected through questionnaires distributed to 55 people selected using purposive sampling techniques. The results of linear regression analysis show that student independence has a significant influence on pocket money planning and financial behavior. At the same time, these two variables also have a significant influence on students' pocket money plans. This study shows how important it is for students to use their pocket money wisely to support academic success and financial stability. These findings will make a major contribution to the development of financial management guidelines for students, especially KIP-K undergraduate students.